NURSES’ PERCEPTIONS OF SPIRITUALITY AND SPIRITUAL CARE AND THE CHALLENGES OF LEARNING SPIRITUALITY - Mulyono, Wastu Adi; Chen, Chung-Hey (Jurnal Keperawatan Soedirman, 2019)
Background. Nurses face barriers both from the environment and from themselves in providing spiritual care. Their perception to the spirituality as well as the spiritual care may contribute into this situation. Aim. This study was to identify the Indonesian nurse’s perception of spirituality and spiritual care. Methods. A cross-sectional survey investigated 273 nurses in Central Java, Indonesia recruited through a convenience sampling. The Spirituality Spiritual Care Rating Scale (SSCRS) Bahasa Indonesia version was applied to measure the nurses’ perceptions. Six other questions related to nurses’ prior knowledge, responsibilities and work experiences were added. To examine the differences in the nurse’s perception of Spirituality (SP) and Spiritual Care (SC), independent t-test and One-Way ANOVA were applied. Findings. Obtained score means were Spirituality 20.0 (2.0), Spiritual Care 46.2 (4.3), and total SSCRS 66.1 (4.5). There was the significant different perception of spirituality and spiritual care as a total, and in subscale of spirituality based on the geographic location (p=0.006). Respondents felt well informed (52.2%), got training (4.8%), capable of delivering spiritual care (70%), mostly considered the patient spiritual need through listening and observing patients by themselves (67.9%). Conclusion. Nurse perception of spirituality and spiritual care were not different based on respondent characteristics, except the respondents’ work geographical area. Challenges in teaching spirituality were confirmed. This study provided basic information in describing Indonesian nurses’ perception on spirituality and spiritual care.